The Ideological Apologetics of the Communist Party during Suppression of Lithuanian National Resistance (1944–1953) - Bagušauskas , Juozas Romualdas (Genocidas ir rezistencija, 2013)
After WWII, the second wave of Stalinist terror initiated by the USR acquired special features in Lithuania. The suppression of national resistance, Sovietisation of the country, and destruction of national identity by combining terror, repression and ideological propaganda took place throughout the country.In the resolutions adopted by the Central Committee of the All-Union Communist Party (Bolsheviks) (AUCP[B]) between 1944 and 1948 on the political situation in Lithuania, the demand was made to destroy the ideology and social basis of the national underground movement and to expel the nation’s aspirations for freedom from its consciousness as soon as possible. Destruction of the spiritual life and identity of the nation was initially carried out by promoting contempt for the nation’s historical past and culture and promoting vandalism. Spiritual and physical terror became the everyday reality of Lithuania’s political life.The national attitudes of the intelligentsia and their attempts to preserve spiritual values that had formed over the years became the cause of never-ending persecution and reprisals against them. One goal was to use a certain part of the intelligentsia for the dissemination of the Soviet ideology. The intention was to bridge the gap that emerged after the repressive measure that caused the emigration of intellectuals to the West. Propaganda and mass political agitation became an important area of ideological activity of the Soviet regime and accompanied spiritual terror and implementation of Communist ideology based on Stalinist dogmas. The Soviet press was full of vitriolic condemnation of the “enemies of the people” and euphoric praise of Stalin and his henchmen. With the help of the press, the Soviet regime hoped to purge ideas about the nation’s freedom from people’s consciousness. Under the veil of Soviet patriotism and proletarian internationalism, Russian nationalism was forced down people’s throats, the role of Russia as the elder brother was constantly emphasised, the spiritual values of the nation were derogated, the nation was humiliated, and it became increasingly difficult to communicate in the native Lithuanian language.The Communist regime created a social environment that it hoped would help to destroy the resistance movement as soon as possible. With the help of the government and the organisations of the Communist Party, society was divided and one social stratum was pitted against the other. By combining repression and ideological measures, the Communist Party eroded the typical mutual relationship of trust that had formed over centuries in the nation.
Keywords: soviet regime; communist party; communist ideology; armed resistance